Renal cell carcinoma needle biopsy: Sowing the seed for later complications?. (30th April 2014) - Laird, Alexander; Couper, Catriona H; Glancy, Stephen; O'Donnell, Marie; Riddick, Antony C P
Abstract : Pathological examination of a radical nephrectomy for papillary renal cell carcinoma showed tumour present within the perinephric fat, with a morphology indicative of iatrogenic tumour cell tracking caused by previous biopsy of the mass. This is a rare complication of percutaneous biopsy, and as this procedure is becoming more common in investigating renal masses, it is important that the professionals are aware of the potential risks posed by renal mass biopsy.